The Diversity Crisis in Software Development - Albusays, Khaled; Bjorn, Pernille; Dabbish, Laura; Ford, Denae; Murphy-Hill, Emerson; Serebrenik, Alexander; Storey, Margaret-Anne (IEEE software, 2021)
This special issue of IEEE Software focuses on diversity and inclusion in software development, presenting research results and best practices for making the field equitable for all. It is well documented that the industry does not provide evenhanded participation conditions. Research has shown that implicit gender biases significantly impact hiring decisions, 1 women disengage faster than men, 2 Palestinian tech entrepreneurs do not have access to Internet-based distribution and payment platforms, 3 software developers with a visual impairment lack tools to navigate code editors, 4,5 and women are sometimes less likely to get their code accepted. 6 Tools, processes, products, and education are not inclusive. Dimensions such as geography, gender, socioeconomic politics, age, ethnicity, and disability shape who can participate in creating technology.